Microshear Bond Strength of Composite Resin to Enamel Treated With Titanium Tetrafluoride and the Carbon Dioxide Laser (10.6 μm): An In Vitro Study - Panahandeh, Narges; Azarsina, Mohadese; Ostad Hossein, Niyayesh; Fekrazad, Reza (Journal of Lasers in Medical Sciences, 2020)
Introduction: The present study aims to assess the microshear bond strength (μSBS) of composite to enamel treated with titanium tetrafluoride (TiF4) and CO2 laser irradiation. Methods: Fifteen human molars were sectioned and their enamel surfaces were abraded. The sections were randomly assigned to 5 groups (n = 15): (CO); control group, (AP); treated with 1.23% acidulated phosphate fluoride (APF) for 4 minutes, (Ti); 4% TiF4 for 1 minute, (L+AP); CO2 laser irradiation (10.6 μm wavelength, 1 W peak power, 10 ms pulse duration, 500 ms repetition time, 0.2 mm beam spot size at the tissue level, 2 cm distance of handpiece tip to tissue surface (DSE, South Cores) followed by 1.23% APF, and (L+ Ti); 10.6μm CO2 laser irradiation followed by 4% TiF4 for one minute. Using Tygon tubes, Z250 (3M/ESPE) composite was bonded to the surface of the samples. The μSBS of the composite to enamel was measured using a microtensile testing machine after 500 thermal cycles. The data were analyzed by one-way ANOVA and the Tukey HSD test (P < 0.05). Results: The mean μSBS was 20.66, 20.21, 13.44, 23.01, and 10.16 MPa in CO, AP, Ti, L+AP, and L+Ti groups respectively. Significant differences were observed between CO and Ti (P = 0.026) and also CO and L+ Ti (P < 0.0001). Conclusion: The application of TiF4 per se and after CO2 laser irradiation on enamel decreased the μSBS of the composite to enamel; on the other hand, APF alone and after laser irradiation did not have any adverse effect on the μSBS of the composite to the enamel.